Sailing Through Troubled Waters: Evidence from Support Discontinuities to Firms in Times of Crisis - Ana Martins; Jo\~ao Pereira dos Santos; Fernando Pozzobon (Institute of Labor Economics (IZA), 2025)
We estimate the causal effect of APOIAR, a targeted COVID-19 support initiative, on firm survival and performance. Using sharp and fuzzy regression discontinuity designs and three administrative datasets, we find that eligible firms experienced a short-term profitability increase in 2021, with exteuro1 of support raising net income by exteuro0.658. These effects did not persist into 2022, and we observe no significant changes in turnover or cost reduction, suggesting the profitability gains were mechanically driven by the subsidy. The funds were particularly used by ex-ante less productive, more indebted firms with limited liquidity
Keywords: H25; H32; D22; L20; 330; grants; small private firms; times of crisis; COVID-19